2003
DOI: 10.1128/aem.69.12.7430-7434.2003
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Assay for Detection and Enumeration ofDekkera bruxellensisin Wine

Abstract: Traditional methods to detect the spoilage yeast Dekkera bruxellensis from wine involve lengthy enrichments. To overcome this difficulty, we developed a quantitative real-time PCR method to directly detect and enumerate D. bruxellensis in wine. Specific PCR primers to D. bruxellensis were designed to the 26S rRNA gene, and nontarget yeast and bacteria common to the winery environment were not amplified. The assay was linear over a range of cell concentrations (6 log units) and could detect as little as 1 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 22 publications
4
78
1
Order By: Relevance
“…Absolute quantification methods by QPCR often use plasmid dilutions (Fontaine and Guillot 2002;Galluzzi et al 2004) or laboratory cultures (Bowers et al 2000;Phister and Mills 2003;Popels et al 2003;Saito et al 2002) to generate a standard curve. Although these standards are relatively easy to prepare, they may not always be appropriate for comparison to natural populations of target cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute quantification methods by QPCR often use plasmid dilutions (Fontaine and Guillot 2002;Galluzzi et al 2004) or laboratory cultures (Bowers et al 2000;Phister and Mills 2003;Popels et al 2003;Saito et al 2002) to generate a standard curve. Although these standards are relatively easy to prepare, they may not always be appropriate for comparison to natural populations of target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The fractional cycle number (Ct) is calculated for each reaction at a point where the fluorescence signal crosses a certain threshold. Several studies have demonstrated the potential of the methodology for the quantitative analysis of microorganisms (Cullen et al 2002;Fontaine and Guillot 2002;Phister and Mills 2003;Skovhus 2004;Suzuki et al 2000;Vaitomaa et al 2003) including harmful algal bloom (HAB) species (Bowers et al 2000;Galluzzi et al 2004;Gray et al 2003;Popels et al 2003;Saito et al 2002) in environmental samples. The basic approach used in these studies is to generate a standard curve using plasmids with the target DNA sequence or DNA extracted from cultures with known concentrations of the target species.…”
mentioning
confidence: 99%
“…Strain A was a reference strain isolated from a distillery plant 37 and identified by the Institute of Hygiene and Epidemiology of Brussels (THEM) as B. bruxellensis strain 6037. A PCR assay, using primers designed to the 26S rRNA gene was used to confirm that the isolated strains belonged to B. bruxellensis species 29 . Specific primers were DBRUXF: 5'-GGATGGGTGCACCTGGTT-TACAC-3' and DBRUXR: 5'-GAAGGGCCACATTCA-CGAACCCCG -3'.…”
Section: Microorganismsmentioning
confidence: 99%
“…Due to the advantages afforded by the technique, it was later extended to yeasts in the clinical setting (1,22,27,29) and in food technology (2,3). Currently, the detection of wine spoil-age yeast using this method is limited to the species Dekkera bruxellensis (21). In the present work, we have developed a real-time PCR to detect and enumerate S. cerevisiae directly in wine samples using the nonspecific fluorescent dye SYBR green.…”
mentioning
confidence: 99%